Implementasi Dompet Digital Polije Berbasis IoT dan Blockchain - MUHAMMAD HAFIDH FIRMANSYAH; Wahyu Kurnia Dewanto; Hariyono Rakhmad (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2024)
urrently, the implementation of IoT devices has been widely utilized by various parties in supporting the increasingly complex aspects of human life. IoT devices have become a favorite among hardware and software developers due to their ease of use and flexibility in adapting to the evolving systems of today. One of the uses of IoT is in the realm of digital economics, where digital economy represents a new way of prioritizing technology and ease in the buying and selling transaction process between sellers and buyers. In the past, payment processes for goods or services used to involve paper money and coins, but nowadays, payments are made using digital media. However, the current digital payment methods still rely on centralized storage technology. Therefore, if the data held at the center is damaged or compromised, it can disrupt the flow of financial transactions, and user data privacy becomes a subsequent concern.